The Application of Rasch Model to Analyse the Validity and Reliability of an Instrument for Reflective Thinking Skills on Topic of Wave-Particle Dualism - Tarpin Juandi; Ida Kaniawati; Achmad Samsudin; Lala Septem Riza (Kappa Journal, 2024)
This study aims to analyse the validity and reliability of an instrument for assessing reflective thinking skills on the topic of wave-particle dualism in modern physics lectures using the Rasch model. The Rasch model was selected for its capability to provide a more in-depth analysis of item performance and respondent ability, as well as to identify misfitting or biased items. The research method employed is a descriptive quantitative approach, utilizing Winsteps software for data analysis. The sample consists of 36 students enrolled in modern physics lectures at a university in West Nusa Tenggara. The results indicate that the instrument has excellent item reliability (0.91) and excellent internal consistency (Cronbach's Alpha 0.86), although the respondent reliability falls into the weak category (0.62). The instrument's validity also meets the Rasch model's acceptance criteria, with infit MNSQ and outfit MNSQ values ranging from 0.5 to 1.5. Further analysis reveals that some items are misfitting and need revision to ensure fairness and consistency in measuring reflective thinking skills. These findings make a significant contribution to the development of more accurate and reliable assessment tools in physics education